Lifestyle, Eating Habits, and Health Behaviors Among Dietary Supplement Users in Three European Countries - Katarzyna Iłowiecka; Monika Maślej; Magdalena Czajka; Adrian Pawłowski; Piotr Więckowski; Tomasz Styk; Michał Gołkiewicz; Adam Kuzdraliński; Wojciech Koch (Frontiers Media S.A., 2022)
Dietary supplements (DS) are used by about 30-50% of adults in developed countries. However, only a few studies have compared the characteristics of DS users in different nations. This study aimed to identify and compare selected health-related behaviors of DS users from three European countries. A total of 3,588 adults (32.08 ± 8.04 years) from Poland (1,030 females, 287 males), Germany (994 females, 190 males), and the United Kingdom (911 females, 176 males) were included in the analysis. The study was based on a self-administered survey consisting of 70 questions regarding baseline characteristics, lifestyle, eating, and health habits. The associations of the obtained results were compared using the Kruskal-Wallis test, Pearson Chi-Square test, and Cramer's V value. The highest percentage of DS users (56.98%, n = 2,044) had a correct body weight, while higher body weight values were observed in 39.19% (n = 1,406). In terms of lifestyle, statistically significant differences (p < 0.05) were noted for alcohol consumption and the level of physical activity. Fruit and vegetables were most often consumed a few times a weeks (34.67%, n = 1,244). A similar result was observed for the consumption of whole grain (37.76%, n = 1,355), dairy (39.99%, n = 1,435), eggs (49.67%, n = 1,782), and meat (51.45%, n = 1,846). Most DS users did not have a chronic disease (66.72%, n = 2,394). Among the other conditions, a frequent occurrence (a few times a weeks) of gastrointestinal problems (28.29%, n = 1,015) and concentration disorders (29.15%, n = 1,046) was noted. Cramer's V values (<0.3) indicated a weak (but significant p < 0.05) relationship between the country of residence and most of the analyzed variables. In conclusion, DS users were characterized by a healthy lifestyle with appropriate behaviors but not healthy eating habits.